UPAYA SES (SENIOR EXPERTEN SERVICE) JERMAN DALAM MENGIMPLEMENTASIKAN PERJANJIAN KERJASAMA INDONESIA-JERMAN BIDANG PENDIDIKAN VOKASI DI INDONESIA - Adina Ramadhani; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The efforts of SES Germany in implementing the Indonesia-Germany Cooperation in the field of Vocational Education in Indonesia. The purpose of this study is to explain; first to know the Indonesian-German Cooperation in the field of Vocational Education, the second to know more about German SES and its movements in Indonesia, third to know the efforts of German SES in implementing the Indonesia-Germany Cooperation in the field of Vocational Education in Indonesia. Germany is a developed country that has been recognized. Vocational education there is very good and has been optimal, even the economy in Germany is still stable due to the hard work of its citizens who have character and have great potential in every skill they have. For that reason, Germany is said to have succeeded in educating graduates. Vocational education.This research is based on the perspective of liberalism, for the level of analysis using groups of individuals to understand the role of one group with other individuals in a particular field, and the theory of Non-Profit Organizations. Collecting data sourced from official websites such as the Indonesian-German Embassy website, the German SES Organization website, and ministries related to research as well as interviews with several parties, for secondary data collected from several news websites, journals, and books published related to the title of the researcher.The results of the research regarding the efforts of SES Germany in implementing the Indonesia-Germany Cooperation in the field of vocational education in Indonesia, namely, SES has helped vocational education in Indonesia through educational institutions from Vocational Schools, Vocational Schools to Polytechnics by providing socialization through workshops, understanding vocational education through training, and communication, effectively facilitate the implementation of the Indonesia-Germany cooperation agreement between Germany SES and Indonesian educational institutions and curriculum proposals. Not only that, Germany SES also provides criticism and suggestions to improve the quality of vocational education in vocational schools so as to produce competent graduates who can be trusted to improve the economy and reduce unemployment in Indonesia. Keywords: Germany SES, Cooperation, Indonesia, Germany, Vocational Education, TVET